ONLINE LEARNING HAS NO EFFECT ON THE LEVEL OF ANXIETY IN NURSING STUDENTS IN THE CITY OF PEKALONGAN - Sri Mumpuni Yuniarsih; I Gede Surya Darma; Rusdi (Jurnal Ilmu Keperawatan Jiwa, 2023)
The online learning method is applied as an alternative to learning during the Covid-19 pandemic. However, the impact of changes in the lecture process experienced during the pandemic risks causes mental health problems to emerge in students. One of the mental health problems that can arise is anxiety. Basic Health Research (Riskesdas) in 2018 showed that 9.9% of people aged 15 years and over or around 19 million people in Indonesia experience emotional mental disorders indicated by symptoms of anxiety and depression. This study aims to determine the correlation between online learning and the level of anxiety in nursing students in the city of Pekalongan. This research uses quantitative methods with an analytical observational design. Nursing student anxiety is measured using the Hamilton Anxiety Rating Scale (HARS) instrument. The sample used in this study was 141 nursing students. The measurement results were analyzed using Kendall's Tau. The results of the study showed that most nursing students participated in hybrid learning, namely 114 people (80.9%). Then most nursing students or as many as 52 people (36.9%) experience mild anxiety. After being tested for correlation with Kendall's Tau, a significance value of 0.876 (p value > 0.05) was obtained, which means that there is no significant correlation between online learning and the anxiety level of nursing students in the city of Pekalongan.